Burden of impaired sleep quality on work productivity in functional dyspepsia. Issue 3 (April 2018) - Matsuzaki, Juntaro; Suzuki, Hidekazu; Togawa, Koji; Yamane, Tsuyoshi; Mori, Hideki; Komori, Takahiro; Masaoka, Tatsuhiro; Kanai, Takanori
Background: Impaired sleep quality is common, and can reduce work productivity in patients with functional dyspepsia (FD). Objective: The objective of this article is to evaluate whether there is a direct association between the presence of FD and the severity of impaired sleep quality, and to calculate the economic loss due to the decreased work productivity associated with sleep quality. Methods: In Study 1, using a web-based survey completed by workers with and without FD, we evaluated impaired sleep quality, work and daily productivity, and the severity of reflux and bowel symptoms. In Study 2, the association between the presence of FD and the severity of impaired sleep quality was validated in a hospital-based cohort. Results: In both Study 1 and 2, although impaired sleep quality was more frequent in participants with FD than in those without FD, the independent association between the presence of FD and the severity of impaired sleep quality was not observed after adjustment for the severity of reflux and bowel symptoms. FD participants with impaired sleep quality reported additional economic loss of 53, 500 Japanese yen/month. Conclusion: Although the association between impaired sleep quality and FD was indirect, concomitant impaired sleep quality could worsen economic loss.